The challenge of defining and treating anemia and iron deficiency in pregnancy: A study of New Zealand midwives' management of iron status in pregnancy and the postpartum period. Issue 2 (24th February 2017) - Calje, Esther; Skinner, Joan
Abstract: Background: Early recognition and management of low maternal iron status is associated with improved maternal, fetal, and neonatal outcomes. However, existing international guidelines for the testing and management of maternal iron‐deficiency anemia are variable, with no national guideline for New Zealand midwives. Clinical management is complicated by normal physiological hemodilution, and complicated further by the effects of inflammation on iron metabolism, especially in populations with a high prevalence of obesity or infection. This study describes how midwives in one New Zealand area diagnose and treat anemia and iron deficiency, in the absence of established guidelines. Methods: Data on demographics, laboratory results, and documented clinical management were retrospectively collected from midwives (n=21) and women (n=189), from September to December 2013. Analysis was predominantly descriptive. A secondary analysis of iron status and body mass index (BMI) was undertaken. Results: A total of 46% of 186 women, with hemoglobin testing at booking, did not have ferritin tested; 86% (of 385) of ferritin tests were not concurrently tested with C‐reactive protein. Despite midwives prescribing iron for 48.7% of second trimester women, 47.1% still had low iron status before birth. Only 22.8% of women had hemoglobin testing postpartum. There was a significant difference between third trimester median ferritin levels in women with BMI ≥25.00 (14 μg/L) and BMI <25.00 (18 μg/L) ( P =.05). Discussion: There was a wide range in the midwives' practice. Maternal iron status was difficult to categorize, because of inconsistent testing. This study indicates the need for an evidence‐based clinical guideline for New Zealand midwives and maternity care providers.